An Assessment of Spatial Distribution and Utilisation of Some Medicinal Plants in Rural Communities of Osun State, Nigeria - Kolawole, AWOYEMI Olakunle; Paul, AWOTAYO Gbenga; A, Ishaq Abdukarim; John, AKINOLA Oluseyi; Ogunsumi, Akintunde A (Indonesian Journal of Geography, 2025)
The utilization of herbal products, particularly by rural communities, remains a vital component of an integrated healthcare system, addressing a myriad of prevailing illnesses and diseases. This study investigates the distribution and usage of medicinal plants in selected rural communities of Osun State, Nigeria. Employing a multi-stage sampling technique, three rural local government areas one from each senatorial district of Osun State were chosen for the study. Data were collected qualitatively through interviews with residents and herbal product merchants in the study areas. The analysis employed a content analysis framework and an interdisciplinary approach. The findings revealed the documentation of 43 plant species, categorized by their family, botanical, common, and indigenous names. Key details, including the plant parts utilized, preparation methods, dosage, and the ailments treated, were also recorded. Leaves were the most frequently used plant parts, followed by barks, roots, and fruits. The most commonly treated ailments included malaria, skin diseases, irregular menstrual flow, and typhoid fever. Additionally, plants such as ginger, turmeric, cinnamon, and black pepper were widely used as immune boosters during the COVID-19 pandemic, particularly in rural communities with limited access to vaccines. The study highlighted that limited access to conventional healthcare and the high cost of orthodox medicine have driven rural populations to rely heavily on herbal remedies, especially during the pandemic. However, factors such as deforestation, urbanization, wildfires, and inadequate documentation of medicinal plants threaten their availability and sustained usage. The study recommends the integration of herbal and orthodox medicine into a cohesive healthcare framework, particularly in light of the COVID-19 pandemic, which disproportionately affected urban populations. Emphasis on the conservation of medicinal plants and the establishment of herbal gardens, even among urban dwellers, is suggested to amplify their role in healthcare and ensure sustainable utilization.Received: 2023-12-20 Revised: 2024-07-11 Accepted: 2025-03-07 Published: 2025-04-27